Foundations of Sequential Art Driven Development - Moravec, Martin; Koubský, Petr, 1961-; Tichý, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2015)
To develop and deliver an innovative and technologically superior product is not enough to succeed when it does not meet the user's daily needs. To develop such a product, you need an abstract and easy to use communication platform for target users, decision makers, and developers, that can also act as a model of the relevant part of the real world displaced by a possible innovation, auxiliary tool in creating a mind map and documentation, and a way of promoting the final product. An instance of such a platform is a sophisticated comic book, itself an instance of sequential art. Not only is it a feature rich and intuitive tool for collaboration of interested parties with different backgrounds, skills and roles, but since it essentially reflects the relevant part of the real world displaced by the innovation, it's pretty easy and quick for a new user to learn and master. Although not limited to such instances, it can be found as an especially useful tool for crowdsourced and open source based projects. This thesis will lay down the much needed theoretical basis for the Sequential Art Driven Development method and offer a practical application of such method, with an open call for contributions from members of the crowd, in the form of a CC0 licensed comic book series "Who is Secret Agent X-9?", a showcase platform for cutting edge technologies like the Bitcoin network and Nemo Mobile operating system.
Vedoucí práce: Petr Koubský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses